2018
DOI: 10.3390/catal8080334
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Combined Cross-Linked Enzyme Aggregates of Ketoreductase and Alcohol Dehydrogenase: An Efficient and Stable Biocatalyst for Asymmetric Synthesis of (R)-3-Quinuclidinol with Regeneration of Coenzymes In Situ

Abstract: Enzymes are biocatalysts. In this study, a novel biocatalyst consisting of magnetic combined cross-linked enzyme aggregates (combi-CLEAs) of 3-quinuclidinone reductase (QNR) and glucose dehydrogenase (GDH) for enantioselective synthesis of (R)-3-quinuclidinolwith regeneration of cofactors in situ was developed. The magnetic combi-CLEAs were fabricated with the use of ammonium sulfate as a precipitant and glutaraldehyde as a cross-linker for direct immobilization of QNR and GDH from E. coli BL(21) cell lysates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 58 publications
0
10
0
Order By: Relevance
“…In addition, the use of extra polymers as a carrier leads to a ‘dilution of activity’ of the immobilized enzymes by introducing a huge portion of non‐catalytic ballast, which consequently results in lower space–time yields and lower productivities 20 . On the contrary, recent studies involving various enzymes immobilized as CLEAs have demonstrated activity recovery of more than 80% 21–23 . Owing to the low activity recovery and specific activity of resin‐bound immobilization, the carrier‐free method was further applied to immobilize muSDR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the use of extra polymers as a carrier leads to a ‘dilution of activity’ of the immobilized enzymes by introducing a huge portion of non‐catalytic ballast, which consequently results in lower space–time yields and lower productivities 20 . On the contrary, recent studies involving various enzymes immobilized as CLEAs have demonstrated activity recovery of more than 80% 21–23 . Owing to the low activity recovery and specific activity of resin‐bound immobilization, the carrier‐free method was further applied to immobilize muSDR.…”
Section: Discussionmentioning
confidence: 99%
“…20 On the contrary, recent studies involving various enzymes immobilized as CLEAs have demonstrated activity recovery of more than 80%. [21][22][23] Owing to the low activity recovery and specific activity of resin-bound immobilization, the carrier-free method was further applied to immobilize muSDR.…”
Section: Discussionmentioning
confidence: 99%
“…[73] It has been used, for example, in the co-immobilizationo faKRED and an ADH. [74] Nature also utilizes enzyme immobilization in the form of self-assembly of protein-based scaffolds, such as cellulosomes and microcompartment shell proteins,t op romote their stabilization and spatial organization,c reate optimum microenvironments forreactionsequences, and increase product yields. [75]…”
Section: Betterformulation and Recycling Of Enzymes Through Immobilizmentioning
confidence: 99%
“…Magnetic CLEAs of other enzymes have been described. For example, m-combi-CLEAs have been prepared from ketoreductases (KREDs) and glucose dehydrogenase for cofactor regeneration with glucose and used in the synthesis of chiral alcohols [149,206,207]. Cui and coworkers [170] prepared m-CLEAs of phenyl alanine ammonia lyase (PAL EC 4.3.1.24) and showed that storage and operational stabilities were superior to those of the simple CLEA.…”
Section: Other Potential Applicationsmentioning
confidence: 99%